2022
DOI: 10.12911/22998993/145410
|View full text |Cite
|
Sign up to set email alerts
|

LandGEM Biogas Estimation, Energy Potential and Carbon Footprint Assessments of a Controlled Landfill Site. Case of the Controlled Landfill of Mohammedia-Benslimane, Morocco

Abstract: Landfills throughout the world are contributing to the global warming problem. This is due to the existence of the most important greenhouse gases in landfill gas; namely, methane and carbon dioxide. Methane has a high potential for energy production and by utilizing the proper technology, large amounts of energy can be extracted from it. This paper deals with the estimation of methane emissions from the controlled municipal solid waste landfill of Mohammedia-Benslimane (MB) in Morocco. Methane emissions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, flaring still contributes to the carbon footprint since CO 2 is released to the atmosphere. A Moroccan landfill reported that installing a landfill gas capture and flaring facility can protect the environment by mitigating greenhouse gas emissions, mainly methane, with an overall reduction of 1.78 million tons of CO 2 equiv in ten years . Of the considered operational strategies, C1, which is 53,752 gha, most nearly represents the carbon footprint of the Fargo landfill.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, flaring still contributes to the carbon footprint since CO 2 is released to the atmosphere. A Moroccan landfill reported that installing a landfill gas capture and flaring facility can protect the environment by mitigating greenhouse gas emissions, mainly methane, with an overall reduction of 1.78 million tons of CO 2 equiv in ten years . Of the considered operational strategies, C1, which is 53,752 gha, most nearly represents the carbon footprint of the Fargo landfill.…”
Section: Resultsmentioning
confidence: 99%
“…A Moroccan landfill reported that installing a landfill gas capture and flaring facility can protect the environment by mitigating greenhouse gas emissions, mainly methane, with an overall reduction of 1.78 million tons of CO 2 equiv in ten years. 75 Of the considered operational strategies, C1, which is 53,752 gha, most nearly represents the carbon footprint of the Fargo landfill. As discussed in Section 2.3.1, Fargo Landfill has a gas collection system, and a large portion of the captured gases is supplied to local industry to be used as fuel.…”
Section: Carbon Footprint Of Fargo Landfillmentioning
confidence: 99%
“…The amount of household solid waste (HSW) in Morocco is increasing due to population growth, urbanization, and changing consumption habits [119]. With a population of [120].…”
Section: Moroccan Production and Competence In Terms Of Recoverable S...mentioning
confidence: 99%
“…The least desirable process in the hierarchy of handling municipal waste is its disposal by landfilling in landfills of a particular type. It includes waste with no value as a potential recycling material and no energy value as a fuel source (Oukili et al 2022). Landfilling is potentially associated with negative environmental impacts of the landfill as a waste disposal facility (Ciuła 2022).…”
Section: Introductionmentioning
confidence: 99%